TEACHING WORLD CITIES IN ENGLISH: METHODS AND STRATEGIES - Samijonova Gulzira Esonboy qizi; Jololdinov Asror Toshtemirovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores effective methods and strategies for teaching the  topic  of  "World  Cities"  in  English.  It  highlights  the  importance  of  integrating language  skills  with  geographical  and  cultural  knowledge,  suggests  engaging classroom  activities,  and  provides  recommendations  for  educators. The  article  also discusses the use of technology, project-based learning, and interactive discussions to enhance students' understanding of global urban centers.